The ethical challenges of leadership - Ciulla, Joanne B. (Henry Stewart Talks, 2010)
The state of ethical leadership in the world, Sources and problems with power, Difficulties with being ethical and effective, Plato's perspective on leader motivation, Managing ego and self-control, The role of compassion, The dangers of success, The function of virtues, duties, and the greatest good, Knowledge and self-knowledge, The nature of doing things right
Reviewed at 2021/01/31